Multilingual English Language Teaching in the Philippines - Jovie D. Espino; Dan Henry F. Gonzales; Isabel Pefianco Martin (Cranmore Publishing, 2021)
In English language teaching (ELT) circles, the English used in the Philippines is traditionally labelled as ESL. However, that label, including the attitudes and practices that it brings, does not accurately capture the complex language situation in the country. In this article, we argue that English education in the Philippines does not account for the multilingual and linguistically diverse context of use in the country. We argue that monolingual perspectives and approaches in ELT continue to dominate the field. Issues of language variation, the existence of varieties of English, and the reality of translanguaging practices are not addressed. From curriculum design, assessment policies and practices, to classroom teaching, ELT in the Philippines persists in taking a one-size-fits-all approach that only privileges so-called 'native speaker' norms. English in the Philippines is best characterized as Englishes. Although an educated Philippine variety of English exists (Bautista, 2008), it cannot be concluded that this is the variety of widespread use across the archipelago. The language situation of the Philippines is complex, thereby eluding labels and categories that only betray a nativespeakerism perspective and a monolingual bias. We argue that Englishes in the Philippines are more appropriately approached as ENL, ESL, and EFL. The implications of these categorizations on ELT in the country are discussed in this paper.